Syn-kinematic sedimentation at a releasing splay in the northern Minwun Ranges, Sagaing Fault zone, Myanmar: significance for fault timing and displacement - Chris K. Morley (2018)
© 2016 The Author. Basin Research © 2016 John Wiley & Sons Ltd, European Association of Geoscientists & Engineers and International Association of Sedimentologists The Sagaing Fault zone is the largest active fault in SE Asia, whose current displacement rate of around 1.8 cm year−1is well-established from GPS data. Yet determining the timing of initiation and total displacement on the fault zone has proven controversial. The timing problem can potentially be resolved through a newly identified syn-kinematic sedimentary section directly related to displacement on the Sagaing Fault in the northern Minwun Ranges. The northern part of the western strand of the Sagaing Fault has a releasing splay geometry that sets up a syn-kinematic oblique-extensional basin in its hangingwall, here called the North Minwun Basin. A series of thick ridges probably composed of alluvial fan and fluvial sandstones dipping between 20 and 70° to the north, and younging northwards comprise the basin fill over a distance of 40 km. Total stratigraphic thickness (not vertical thickness) is estimated at 25 km. The basin in terms of depositional geometries, large displacements, and large stratigraphic thickness and appearance on satellite images has parallels with the extensional Hornelen basin, Norway and the strike-slip Ridge Basin, California. Minimum likely displacement on the fault strand is 40 km, and may possibly be in excess of 100 km. The remote and inaccessible basin has yet to be properly dated, likely ages range between Eocene and Miocene. When dated the basin will provide an important constraint on the timing of deformation. The potential for this basin to constrain the timing and displacement along the northern part of the Sagaing Fault has not been previously recognised.